Role of Physical Therapy Intervention and Gene Therapy on Muscular Dystrophies, Current Status and Future Perspectives: A Narrative Review : Role of Physical Therapy Intervention and Gene Therapy - Abid, Hafsa; Shah, Saleh; Ahmed, Ali; Habib, Nazira; Bibi, Mah; Ibrahim, Muhammad (Pakistan Journal of Health Sciences, 2024)
Muscular dystrophies form a collection of genetic disorders marked by progressive muscle weakness and degeneration. The identification of the majority of responsible genes has enabled precise diagnosis and subtype-specific anticipatory care. Over the years, various therapies, encompassing genetic, cellular, and pharmacological approaches, have emerged for muscular dystrophies. This narrative review thoroughly explores the ongoing developments in muscular dystrophy therapeutics, including antisense therapy, CRISPR, gene replacement, cell therapy, based gene therapy Adeno-associated viral vector (AAV), and disease-modifying small molecule compounds. The review is particularly significant as it reflects advancements in supportive medicine that have altered the standard of care, leading to an overall improvement in the quality of life, clinical course and survival for affected individuals. In this study, our focus is on the clinical manifestations, molecular pathogenesis, diagnostic strategies, and therapeutic advancements related to this group of conditions. The study involved the review of 20 pertinent English-language articles, publications, reports, and online resources.